Utilization of walnut male flowers (Juglans regia l.) as a functional ingredient in biscuits: impacts on dough rheology, nutritional composition, glycemic response, and sensory attributes - Qin, Guoshuang; Li, Yajing; Sun, Jian; Wang, Zhenxing; Nie, Jinggui; Kong, Kin Weng; Ismail, Amin; Si, Yongyu; Zhang, Xuechun (John Wiley and Sons, 2026)
Walnut male flowers (WFs), an underutilized by-product of walnut (Juglans regia L.) processing, are rich in nutrients and contain bioactive compounds with potential health benefits. This study examined the effects of partially substituting wheat flour with WFs (0%, 1%, 3%, 5%, 7%, and 10% w/w) in biscuit formulations on dough rheology, nutritional profile, texture, microstructure, glycemic response, and sensory characteristics. The addition of WFs significantly increased both the storage modulus (G′) and the loss modulus (G″) of the dough, indicating an improvement in its viscoelastic properties. Nutritional composition analysis revealed elevated protein, ash, and dietary fiber contents, accompanied by reduced total sugar and soluble carbohydrate levels. Texture profile analysis revealed decreased hardness and increased crispness, supported by scanning electron microscopy (SEM) observations of a more porous microstructure. The predicted glycemic index (pGI) decreased by up to 16% with 10% WFs substitution, which may be due to dietary fiber–mediated starch encapsulation and phenolic inhibition of α-glucosidase activity. Sensory evaluation indicated that biscuits containing 5% WFs received the highest overall acceptability, achieving a balance of desirable color, texture, and flavor. The results indicate the potential of WFs as a functional ingredient for developing low–glycemic index baked goods and support the sustainable use of agricultural by-products.